Nutrición mineral de arroz - Mejía de Tafur, María Sara; Menjivar Flores, Juan Carlos (International Center for Tropical Agriculture, 2010)
Mineral nutrition of rice Several aspects related to the mineral nutrition of rice are reviewed in detail, with emphasis on the functions and distribution of essential plant elements (nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, silicon, iron, zinc, copper, manganese, molybdenum, and boron). In rice, as in all crops, an adequate nutrition implies a balance in the amounts of the different nutrients applied to the soil and absorbed by the plant. An imbalance in this nutrient ratio can directly cause the presence of insect pests and disease susceptibility in plants, which will undoubtedly affect final crop yield.